Are complete metal-organic frameworks really responsible for improving the performance of high-temperature proton exchange membranes?. (January 2023) - Wei, G.; Liu, Y.; Wu, A.; Min, Y.; Liao, Z.; Zhu, R.; Liang, Y.; Wang, L.
Abstract: Constructing continuous proton transfer channels used metal-organic frameworks (MOFs), which can effectively improve proton conductivity of proton exchange membrane, have recently attracted a lot of attentions. MOFs have relatively harsh operating environment in phosphoric acid-doped (PA-doped) high-temperature proton exchange membranes (HTPEMs). However, there are few reports on the stability and state of MOFs in HTPEMs after PA doping. In this work, a series of MOFs (UIO-66, UIO-66-COOH, UIO-66-NH2, UIO-66-SO3 H, MIL-101(Cr), and MIL-53(Al)) are selected to investigate their stability via simulating the operating environment for the first time. Composite membranes based on the MOFs are prepared to explore the influence of the stability and state of MOFs on HTPEMs properties. These results indicate that proton transfer channels are constructed in two different styles. After soaking in PA of UIO-66, UIO-66-COOH, MIL-101(Cr), and MIL-53(Al) at 160 °C, metal ions leave the ligands and dissolve, while the ligands are kept in the membranes. These ligands can provide proton transport sites in the membranes and help to construct proton transfer channels. UIO-66-NH2 and UIO-66-SO3 H are dissolved completely in PA, leading to continuous nanopores. The proton transfer channels are constructed using the nanopores. From the results, we can infer that constructing proton transfer channels is an effectively method to improve the membranes performance, but the transmission mechanism needs to be revealed carefully. Graphical abstract: Image 1 Highlights: Complete metal–organic framework (MOF) is difficult to exist under high-temperature phosphoric acid condition. After MOFs disintegrated, proton transfer channels are constructed by the residual ligands or continuous nanopores. For insoluble ligands, large ligands proportion and side groups quantity can significantly improve performance of high-temperature proton exchange membranes. For soluble ligands, the nanopores left by MOFs have a strong siphoning effect, which is beneficial for phosphoric acid retention. Blending MOFs is still an effective strategy to improve the performance of high-temperature proton exchange membranes.